Islam and Support for Gender Inequality among Women in Turkey: Comparing Attitudes across Institutional Contexts (American Journal of Islam and Society, 2018)
Turkey has been characterized as a nation that exhibits an amalgam of Eastern and Western cultural values. For a lengthy period of time, Turkey had prohibited Muslim women’s wearing of the veil in many public venues. Yet, the vast majority of this nation’s citizens are highly devout Muslims. Our study uses these paradoxes as a springboard for investigating early twenty-first century religious influences on Turkish Muslim women’s attitudes toward gender inequality. We introduce the theoretical construct of diversified institutional contexts, arguing that gender is not simply a singular institutional form but rather ebbs and flows with women’s mobility across variegated institutional settings. We hypothesize that religious devotion among Muslim women in Turkey circa the year 2000 will be associated with greater support for gender inequality across several institutional domains, namely, family, education, the workplace, and politics. In addition, we anticipate that as women move across these institutional contexts, they will encounter distinctive gender norms that shape their social opportunities. The public secularism and privatized religious climate of Turkey will yield the most pronounced religious support for gender inequality in family life when compared with other institutional contexts. These hypotheses are proposed for Turkey at the turn of the twenty-first century, prior to the rise of the current ruling party, and are supported with data analyzed from the 2001 wave of the World Values Survey. We conclude by specifying implications of these findings and promising directions for future research, including the continued monitoring of recent developments in this politically changing nation.